FAMILY AND CHILDREN IN LIFE-SETTINGS OF DAGHESTANIANS (ACCORDING TO THE RESULTS OF A SOCIOLOGICAL SURVEY) - Zagirova, El'vira Mahacevna (History, Archeology and Ethnography of the Caucasus, 2018)
The paper examines the position and status of the family in the social environment, as well as its perception in modern Russian society. Against the backdrop of hard demographic processes in Russia, the decline in the birth rate, the noticeable deterioration in the situation actualizes the study of the role and place of the family and children in the life settings of the Daghestan people. The urgency of this problem is determined by socioeconomic transformations in Russian society, which are expressed, along with other problems, in the planning of the number of children, with orientation to one-child family, with the dominance of other socially significant desires. The basis for changing reproductive settings in the modern Daghestan family is not only a change in the reproductive behavior of the woman herself, but also a reassessment of her own maternal role. The institution of family has been undergone fundamental changes, hence the scientific understanding of the reproduction issue, the attitude to the bereaved families, the evaluation of family behavior focused on voluntary childlessness, and a study of, being lost nowadays, importance of «large family» are of great scientific importance. According to the results of the research, it was established that in the mass consciousness of the Daghestan peoples there is a negative attitude toward voluntary childlessness, while, at the same time, designating the woman's destiny to be a mother. However, the respondents with understanding and sympathy look at childless families who found themselves in this category for objective reasons.
Keywords: Daghestan family; childless family; voluntary childlessness; family crisis